3 Cardiac Diagnoses in Survivors of Cardiac Arrest with Culprit-Free Coronary Angiograms. (31st May 2014) - Williams, Howell J; Joshi, Abhishek; Kirkby, Claire; Castiello, Teresa; Stephenson J, Edward; Wragg, Andrew; Sekhri, Neha; Schilling, Richard J; Mohiddin, Saidi A
Abstract : Background: Knowledge of cardiac arrest (CA) causes other than coronary artery disease is derived predominantly from post-mortem studies, identifying hypertrophic cardiomyopathy (HCM) as the commonest diagnosis. Management of CA survivors mandates definite attempts towards diagnosis, particularly as the cause may be inherited with implications for family screening. Our approach to non-ischaemic CA includes cardiac magnetic resonance (CMR) and electrophysiological (EP) assessment. Methods: We identified 102 consecutive CA survivors (VT/VF CA or VT requiring cardioversion) without obstructive CAD who presented to our institution to evaluate this strategy (2008–13). Results: Mean age was 51 years (range 19–80), 66% were male; median CA to CMR interval was 10 days (IQR 12). CMR findings contributed to a structural diagnosis in 54 (53%). In the remaining 48, EP studies in 34 contributed to a diagnosis in 7 (7%). Accordingly, we identified a diagnosis in 61 patients (60%). In the 54 with structural disease, dilated cardiomyopathy (DCM) was diagnosed in 21 (39%), myocarditis 16 (30%–4 with sarcoid), missed myocardial infarction 8 (15%), HCM 5 (9%), arrhythmogenic right ventricular cardiomyopathy in 2 (4%), amyloid in 1 (2%) and severe valve disease in 1 (2%). EP causes were identified in 7: accessory pathways (3), long QT (3) and Brugada Syndrome (1). Only 4 patients had previous cardiac diagnoses (all DCM). In the 41 with no clear diagnosis, CMR findings of uncertain significance were detected in 15 patients; tissue abnormalities in 7, mild left ventricular (LV) hypertrophy in 3 and mild LV systolic impairment in 5. DCM later developed in 2. Follow up data was available for 84 patients; 64 (76%) had an ICD implanted, 2 died before implantation and 2 declined. CA risk was considered treated or transient in the remainder. During mean follow-up of 31-months, appropriate ICD therapy was received by 12/36 (33%) structural diagnosis patients, 1/4 (25%) EP patients and 6/24 (25%) patients with no cardiac diagnosis. Conclusions: MRI and EP studies are key components of the investigation of non-ischaemic CA survivors, leading to diagnosis in 60% of patients. Our study describes heterogeneous diagnoses, with DCM and myocarditis the commonest identified. Notably, 40% of CA survivors have no cardiac diagnosis, have high rates of ICD therapy and may have pre-phenotypic cardiomyopathy.